JBAH 2021
DOI: 10.7176/jbah/11-4-06
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination Levels in Clams (Galatea paradoxa, Born 1778) and Surface Sediments from Mono River Estuary, Togo, and its Health Implications

Abstract: Heavy metal pollution in aquatic ecosystems is one of the most important threats of human health and food chain. Thus, in this study, the level of Cd, Fe, Hg, Mn, Pb and Zn accumulation in surface sediments and in Galatea paradoxa, were investigated to estimate their potential health risks via consumption to residents alongside the Mono river, Togo-Benin border. Samples were collected at two fishing areas and analyzed using flame atomic absorption spectrophotometry Moreover, the likely health risks developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Tuzen (2003) and Ahmad et al (2010) opted that the accumulation of metals is generally found to be species specific and could be related to their feeding habits and bio-concentration capacity of the species. Ross (2014) and Kondo et al (2021) reported that heavy metal concentrations in fish may likely be dependent on many factors such as duration of exposure to contaminants, feeding habits, concentrations of contaminants in their habitat, water chemistry, contamination of fish during handling and processing, sex, weight, season of sampling etc. Rainbow (2002) The possible reasons for this variation could be due to the differences in the water bodies the clams were collected, type of effluents discharged into the water and the type of anthropogenic activities carried out in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Tuzen (2003) and Ahmad et al (2010) opted that the accumulation of metals is generally found to be species specific and could be related to their feeding habits and bio-concentration capacity of the species. Ross (2014) and Kondo et al (2021) reported that heavy metal concentrations in fish may likely be dependent on many factors such as duration of exposure to contaminants, feeding habits, concentrations of contaminants in their habitat, water chemistry, contamination of fish during handling and processing, sex, weight, season of sampling etc. Rainbow (2002) The possible reasons for this variation could be due to the differences in the water bodies the clams were collected, type of effluents discharged into the water and the type of anthropogenic activities carried out in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The heavy metals originating from pollution sources in the upper and middle reaches would be drained downstream (the lower reaches), where they would be added to local pollution to produce high concentrations of heavy metals (Blanc et al, 2005;Damy, 2011;Moruf and Akinjogunla, 2019). The phenomenon of water releases from the Nangbéto Dam, responsible for high erosion in the basin (Amoussou et al, 2012), would facilitate this accumulation of metals in the lower course (Kondo et al, 2021). High-water velocity in a river encourages bank erosion, releasing particles (including organic matter, metals, etc.)…”
Section: Characterization Of Stations: Relationship Between Physicoch...mentioning
confidence: 99%
“…However, there is a lack of data on water and sediment quality in other parts of the basin and on the quality of fishery products throughout the basin. As the lower reaches is the final receptacle for pollution from the upper and middle reaches (Kondo et al, 2021), and fish is the main source of protein for riverside populations, there is an urgent need to assess the quality of the biotope of the lower reaches and the quality of the flesh of the fish species most consumed by riverside residents. This study aims to assess the physicochemical quality of the water and the concentrations of heavy metals in the sediment, water, and flesh of the most abundant fish species and those most appreciated by residents in the lower reaches of the Mono basin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation